Literasi Meningkatkan Kecerdasan Bermedia Bagi Kaum Millenial - Rafinita Aditia; Fonika (Connected: Jurnal Ilmu Komunikasi, 2021)
This study aims to collect data based on reference books and research journals and analyzes carried out simultaneously. The data analysis used in this research is an inductive qualitative analysis technique which is carried out by exploring and analyzing the research focus. The findings of this research are carried out comprehensively and relate them to various concepts and literature studies related to research results. Media literacy provides space for the community to be able to sort and choose content or information according to their needs and not get carried away in the form of negative learning. Families who are able to educate and provide the first education for their children can form positive children's characters and are able to think critically, children who can sort out content and information according to their needs are not easily influenced or just participate in spreading and understanding content that contains social conflicts or just information which is going viral